2009
DOI: 10.1111/j.1741-6787.2009.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Prevention of Surgical Infections in Operating Theaters

Abstract: It is suggested that increased compliance to infection control guidelines for surgical infections in OTs would facilitate providing best practice and evidence-based care. There is a need for further research to determine why there is a difference between what is practiced and what guidelines indicate should be practiced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Osborne (2003) in Australia, Demir (2009) andHosoglu et al, (2011) in Turkey found that there was a relationship between the low compliance rate and the participant's demographic characteristics in terms of age, gender and religion. This is consistent with Ayed, Equait, Fashafsheh and Ali's (2015) study in Palestine and Fashafaheh et al's study in Egypt (2015) according to age, gender, years of experience, nursing education, education training but is inconsistent with Ayed et al (2015), Efstathiou et al's, study (2011a) and Mortada & Zalat's (2013), in terms of gender.…”
Section: The Effects Of Characteristics Of Nurses On Compliance With mentioning
confidence: 99%
“…Osborne (2003) in Australia, Demir (2009) andHosoglu et al, (2011) in Turkey found that there was a relationship between the low compliance rate and the participant's demographic characteristics in terms of age, gender and religion. This is consistent with Ayed, Equait, Fashafsheh and Ali's (2015) study in Palestine and Fashafaheh et al's study in Egypt (2015) according to age, gender, years of experience, nursing education, education training but is inconsistent with Ayed et al (2015), Efstathiou et al's, study (2011a) and Mortada & Zalat's (2013), in terms of gender.…”
Section: The Effects Of Characteristics Of Nurses On Compliance With mentioning
confidence: 99%
“…Three articles comprise a cross-sectional survey evaluating HCW compliance rates vis-à-vis UP/SP, [27][28][29] while the other four studies are mixed designs. [30][31][32][33] Cutter and Jordan conducted two studies in the area of HCWs compliance toward UP/SP, which makes their outcomes more convincing and trustworthy, as multiple studies by authors in the same area gives them greater expertise in the field.…”
Section: Compliancementioning
confidence: 99%
“…21,24,28,[30][31][32][33] Ethical considerations are essential to the validity and variability of any study. 34 Obtaining informed consent from participants is not required with this design, because using a questionnaire is considered less intrusive in a participant's life, and because anonymity can be assured with questionnaires.…”
Section: Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Esse tipo de infecção pode prolongar a hospitalização do paciente de cinco a 20 dias, e aumentar substancialmente os custos (DEMIR, 2009;UÇKAY et al, 2011;HALVORSON et al, 2012 Nos EUA, a ISC representa a terceira topografia de infecção mais freqüente, correspondendo a 15% de todas as IRAS (MANGRAM et al, 1999;RABHAE;RIBEIRO FILHO, 2000;PAVANELLO et al, 2005;ANVISA, 2009ANVISA, , 2010PARIKH et al, 2010 (MANGRAM et al, 1999;WEIGELT et al, 2010;HENRIKSEN et al, 2010;MOUCHA et al, 2011;TANNER et al, 2012 (GARNER, 1986;MANGRAM et al, 1999).…”
unclassified